Diferenciação ecológica em Clibanarius symmetricus (Crustacea: Decapoda: Anomura) de acordo com traços comportamentais - Garcia, Frederico Alekhine Chaves (2020)
Variation in behavioural traits is a raw in which natural selection acts, because individuals with diferente levels of behavioural activity may choose diferente resources, like microhabitat, food and reproductive partner. This variation may lead to diferentiation of ecological niche between individuals in a same population. Thus, this research analyzed the intraespecific variation in microhabitat preference in Clibanarius symmetricus. Chapter I verified influence of captivity time in activity level in C.symmetricus. 60 individuals were observed for boldness and exploration in two periods: initial (right after thay have been collected) and final (after 30 days of captivity).Boldness was estimated from the time that na individual spent to re-emerge after being manipulated. Exploration was calculated as the time individual spent moving around the arena. Exploration decreased after captivity time, but boldness did not change. We concluded that activity level was influenced by captivity time. Chapter II analyzed relation between predation risk and behavioural variability in boldness and exploration in C. symmetricus. 140 individuals were collected in four diferente substrates (“sand”,“mud”, “oyster bank” and “mud with root”) were observed for boldness and movement. Individuals collected in sand and mud had higher level of activity, which indicates a relation between acitivity level and microhabitat occupancy. This corroborrates the idea that individuals with different behavioural levels may choose diferente microhabitat and lead to an ecological diferentiation. Individuals showed high behavioural plasticity, so that they could adapt to environment with constant changes. It was possible to identify relation between behavioural plasticity and predation risk. Chapter III related_behavioural plasticity with individual specialization in microhabitat. It was used data of behavioural traits and microhabitat preference from 60 individuals. It was verified high level of individual specialization. This indicates a variation in individual niches in order to reduce intraespecific competition. We concluded that microhabitat’s preference, an important aspect of C. symmetricus ecology, is related to individuals behavioural traits. Interespecific variability in behavioural traits contributed to the increase in individual specialization, with population containing specialists and generalists individuals.Therefore, we verified that the study individuals variations contributed to the understanding of population dynamic of the specie.